2016
DOI: 10.1111/lam.12623
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of spent craft brewer's yeast by caprine rumen hyper ammonia‐producing bacteria

Abstract: Spent brewer's yeast has long been included in ruminant diets as a protein supplement. However, modern craft beers often include more hops (Humulus lupulus L.) than traditional recipes. These compounds include α- and β- acids, which are antimicrobial to the rumen hyper ammonia-producing bacteria (HAB) that are major contributors to amino acid degradation. This study demonstrated that hops acids in spent craft brewer's yeast protected protein from destruction by HABin vitro. These results suggest that the spent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 19 publications
1
17
0
1
Order By: Relevance
“…Other compounds derived from hops include α-and β-acids, which have a strong antimicrobial activity [78]. The α-acid content ranges between 167 and 2074 µg/g, with an average related to the total hop acid between 487 and 2557 µg/g.…”
Section: Brewing Technologymentioning
confidence: 99%
“…Other compounds derived from hops include α-and β-acids, which have a strong antimicrobial activity [78]. The α-acid content ranges between 167 and 2074 µg/g, with an average related to the total hop acid between 487 and 2557 µg/g.…”
Section: Brewing Technologymentioning
confidence: 99%
“…After arrival at the laboratory, rumen cell suspensions were prepared as previously described (Harlow et al, 2016). After arrival at the laboratory, rumen cell suspensions were prepared as previously described (Harlow et al, 2016).…”
Section: Rumen Cell Suspension Preparationmentioning
confidence: 99%
“…When rumen digesta were needed for the ex vivo experiment, samples (~0.5 kg) were collected from each steer individually and transported to the laboratory in an airtight, insulated container within 1 h of collection. After arrival at the laboratory, rumen cell suspensions were prepared as previously described (Harlow et al, 2016). Briefly, the rumen digesta samples were squeezed through muslin to remove large plant particles and were subjected to a low-speed centrifugation (100 ´ g, 10 min) to remove the smaller plant particles and protists (Sorvall RC-6; Thermo-Fisher Scientific, Waltham, MA).…”
Section: Rumen Cell Suspension Preparationmentioning
confidence: 99%
“…There is interest in brewery ruminant co-products with high levels of hop phytochemicals. Some results have shown that spent brewers' yeast inhibited rumen ammonia and methane production [25] [26]. Another DOI: 10.4236/aim.2019.912063 990 Advances in Microbiology study indicates that older stored hops are adequately antimicrobial for feeding applications even after they are no longer desirable by brewers [27].…”
Section: Discussionmentioning
confidence: 99%